Gangguan Pola Nafas Tidak Efektif Pada Pasien Congestive Heart Failure (CHF) - Wilantika Ida Wardani; Yuyun Setyorini; Akhmad Rifai ((JKG) Jurnal Keperawatan Global, 2018)
Abstract Background: Congestive Heart Failure (CHF) is the heart failure in pumping blood so that the blood supply containing oxygen and nutrients to the entire body tissues is inhibited and causes shortness of breath. Problems that arise that the breath pattern is not effective and can be arranged intervention one of them assess the frequency of breath depth. Acquire a real picture and experience in patients with Congestive Heart Failure (CHF). Methods: The type of research used in the preparation of scientific papers is the type of descriptive research and case study design with the approach of nursing care. The number of patients who became the study respondents amounted to two people. Result: Based on observation result, it is concluded that with the same nursing diagnosis and done the same implementation there is difference of result and response between group of intervention with control group. Suggestion. Suggestions put forward in this study is the need to pay attention to the accuracy of the assessment to determine the priority problems that occur in patients and the principle of ONEC (Observation, Nursing Treatment, Education, Collaboration) on the intervention.